2014
DOI: 10.1186/1743-0003-11-160
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contralesional robot-assisted hand training in patients with unilateral spatial neglect following stroke: a case series study

Abstract: BackgroundA reduction of hemispatial neglect due to stroke has been associated with activation of the contralesional hand in the contralesional hemispace. Robot-assisted upper limb training was found to effectively improve paretic arm function in stroke patients. To date no proof of concept of robot-assisted hemispatial neglect therapy has been reported in literature. This study aimed to determine whether robot-assisted left (contralesional) hand activation alone could lead to an improvement in hemispatial neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 29 publications
5
35
0
Order By: Relevance
“…Recently, a case study reported that the extent of hemispatial neglect decreased after passive joint movements of the left hand using a hand rehabilitation robot for two weeks in patients with left hemispatial neglect [34]. Although this case series study was the first study to use rehabilitation robots in the treatment of hemispatial neglect, it was limited in that there was no control group and only passive movements of the hand were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a case study reported that the extent of hemispatial neglect decreased after passive joint movements of the left hand using a hand rehabilitation robot for two weeks in patients with left hemispatial neglect [34]. Although this case series study was the first study to use rehabilitation robots in the treatment of hemispatial neglect, it was limited in that there was no control group and only passive movements of the hand were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these devices are normally restricted in clinical environments and are not suitable for use as an at-home assistive device that can provide assistance for activities of daily living (ADL) and task-specific training. In order to design exoskeletons that are more wearable and lightweight, alternative approaches that utilize compliant materials such as cables [9][10][11] and soft elastomeric actuators have been adopted. These approaches do not require complicated mechanical setups, which reduce the setup time and the possibility of misalignment.…”
Section: Introductionmentioning
confidence: 99%
“…Each task was repeated 10 times (trials) for each condition. In the Exoskeleton trials, the device was worn on the right hand and the subject was instructed to restrain any voluntary hand motion in order to let the exoskeleton autonomously [11] Thumb, medium, ring Flexion 12 ∼650 ∼50 Absent Limited Nycz et al [12] All Flexion, extension n/a n/a ∼50 Absent Absent In et al [13] Thumb, index, medium Flexion, extension 20 n/a 194 Absent Absent Kang et al [14] Thumb, index, medium Flexion, extension 29.5 1630 ∼50 Absent Limited Polygerinos et al [15] All Flexion 40 3300 285 Full Absent Varalta et al [16] All Flexion, extension n/a 5000 ∼50 Full Absent implement the task. During the experiment, the beginning and the end of each trial were signaled by graphical cues on a computer screen.…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…Several studies have shown that manual tasks induce changes, with respect to baseline states, in the spectral power of sensorimotor cortex areas, for two characteristic frequency bands: µ ( [8,12] Hz) and β ( [16,32] Hz). Such results have been confirmed in invasive [23] and non-invasive [24] studies.…”
Section: Brain-machinementioning
confidence: 99%
See 1 more Smart Citation